Biaxially oriented polyolefin film
By setting two layers with different contents of 4-methyl-1-pentene polymer on the surface of a biaxially oriented polyolefin film, the problems of film welding and deformation under high temperature conditions are solved, and the heat resistance and interlayer adhesion of the film are improved, making it suitable for demolding and process film applications under high temperature conditions.
Patent Information
- Application Number
- CN202580025080.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-12
- Filing Date
- 2025-03-19
- Publication Date
- 2026-11-03
AI Technical Summary
Existing biaxially oriented polyolefin films are prone to welding and deformation at high temperatures, making them unsuitable for use as release films and process films, and they also lack interlayer adhesion.
Differential scanning calorimetry (DSC) was used to determine that the heat of fusion in the range of 175~190℃ accounted for 10%~70% of the heat of fusion in the range of 30~190℃. Two layers with different contents of 4-methyl-1-pentene polymer were set on the membrane surface, with the high-content layer being designated as layer B, located on at least one membrane surface. Layer B was mainly composed of 4-methyl-1-pentene polymer.
It effectively inhibits film deformation and welding in high-temperature environments, improves interlayer adhesion, and ensures the film's heat resistance and demolding properties, making it suitable for use as a release film and process film.
Smart Images

Figure CN123036209A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to biaxially oriented polyolefin films with excellent heat resistance. Background Technology
[0002] Biaxially oriented polyolefin film is obtained by biaxially stretching unstretched polyolefin sheets. It boasts excellent productivity and film thickness accuracy, making it suitable for various applications such as packaging and tapes. Furthermore, due to its superior mechanical properties and mold release properties, biaxially oriented polyolefin film is also suitable as a release film and process film for various components such as plastic products, building materials, and optical components.
[0003] The required properties of the aforementioned release films and process films are appropriately set according to their applications. However, with the increasing performance of materials and higher productivity, molding and process temperatures tend to rise year by year, thus increasing the importance of heat resistance. Furthermore, there are applications where the release of water vapor is undesirable, such as for process films used in secondary battery electrodes or metal sputtering. In these applications, biaxially oriented polyolefin films with low moisture content are desirable.
[0004] However, in cases such as processing components formed on release films or manufacturing components using process films, most processes require heating at temperatures exceeding 160°C for at least several minutes. Under such conditions, even polypropylene, a polyolefin with relatively high heat resistance, is prone to welding and deformation, which can damage the quality of the component formed on the film. Therefore, in such situations, using biaxially oriented polyolefin films as release films or process films is very difficult.
[0005] As one of the indicators of heat resistance, weld resistance is also important. To improve this, studies have been conducted on forming a layer on the film surface containing a 4-methyl-1-pentene polymer or its copolymer, which is a resin with a high melting point. However, when these resins are laminated with other polyolefins, the difference in their melting points and suitable stretching temperatures can easily lead to incomplete layer formation and film breakage, thus becoming a problem. In addition, the weak adhesion between these resins and other polyolefins makes interlayer delamination prone to occur between the substrate and the surface layer, hindering their performance as a release film or process film.
[0006] In the aforementioned cases, for example, Patent Documents 1 and 2 describe the following: a layer formed by laminating a 4-methyl-1-pentene polymer or its copolymer into a polypropylene layer as a surface layer is used to improve interlayer adhesion and mold release at room temperature. Furthermore, Patent Document 3 describes the following example: a matte polypropylene layer containing a propylene block copolymer is laminated, and the molecular weight of the inner polypropylene layer is adjusted, thereby improving heat-sealing properties.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: International Publication No. 2018 / 097161
[0010] Patent Document 2: Japanese Patent Application Publication No. 2014-30974
[0011] Patent Document 3: Japanese Patent Application Publication No. 2015-44406 Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] However, the films obtained by the methods described in Patent Documents 1 and 2 are not designed for use in high-temperature environments, and welding and deformation become problematic at high temperatures. Furthermore, for the film obtained by the method described in Patent Document 3, since it only assumes exposure to high temperatures for a very short time, there is a possibility of insufficient suppression of heat shrinkage and welding. In other words, polyolefin films obtained by these methods are difficult to use as release films or process films in high-temperature environments.
[0014] Therefore, the objective of this invention is to solve the above-mentioned problems. That is, the objective of this invention is to provide a biaxially oriented polyolefin film that can be used even in high-temperature environments where conventional biaxially oriented polyolefin films cannot be used as release films or process films.
[0015] Problem-solving methods
[0016] To address the aforementioned issues, the biaxially oriented polyolefin film of the present invention comprises the following structure: A biaxially oriented polyolefin film characterized in that the proportion S of the heat of fusion in the range of 175-190°C (obtained by differential scanning calorimetry) to the heat of fusion in the range of 30-190°C is 10%-70%, and it comprises two layers with different contents of 4-methyl-1-pentene polymers. In one of the two layers, the layer with a relatively lower content of the 4-methyl-1-pentene polymer is designated as layer A, and the layer with a relatively higher content of the 4-methyl-1-pentene polymer is designated as layer B. Layer B is located on at least one film surface, and layer B contains the 4-methyl-1-pentene polymer as a main component.
[0017] Invention Effects
[0018] According to the present invention, a biaxially oriented polyolefin film can be provided that is suitable for use even in high-temperature environments where conventional biaxially oriented polyolefin films cannot be used as release films or process films. Attached Figure Description
[0019] Figure 1This is a schematic diagram illustrating the pressurization method used in evaluating heat resistance properties. Detailed Implementation
[0020] The biaxially oriented polyolefin film of the present invention is characterized in that the proportion S of the heat of fusion in the range of 175-190°C (obtained by differential scanning calorimetry) to the heat of fusion in the range of 30-190°C is 10%-70%, and it comprises two layers with different contents of 4-methyl-1-pentene polymer. In these two layers, the layer with a relatively lower content of the 4-methyl-1-pentene polymer is designated as layer A, and the layer with a relatively higher content of the 4-methyl-1-pentene polymer is designated as layer B. Layer B is located on at least one film surface, and layer B contains the 4-methyl-1-pentene polymer as a main component. The polyolefin film of the present invention will be described below.
[0021] It should be noted that when a numerical range is expressed as "a~b" in this invention, the numerical range includes the values at both ends a and b. Only when the unit is recorded after the numerical range a~b, the unit is the same throughout the numerical range.
[0022] Here, "film" refers to a sheet-like molded body primarily composed of thermoplastic resin. "Main component" refers to the component contained in a proportion exceeding 50% by mass but less than 100% by mass when all components of the target material (film, layer, etc.) are considered as 100% by mass. "Biaxial orientation" refers to molecular orientation in two orthogonal directions. Biaxially oriented films can be obtained by stretching a sheet in two orthogonal directions (usually the length and width directions). It should be noted that the length direction refers to the direction in which the film travels during the manufacturing process (the winding direction in the case of a film roll), and the width direction refers to the direction orthogonal to the length direction within the film surface.
[0023] Polyolefin membranes refer to membranes whose main component is an olefin resin. However, when multiple olefin resins are included, even if the content of each individual olefin resin is less than 50% by mass of the total membrane, if the total content of all olefin resins exceeds 50% by mass, it is considered equivalent to a polyolefin membrane. Here, olefin resins (e.g., polypropylene resin, 4-methyl-1-pentene polymers) refer to resins containing more than 50% but less than 100% of structural units derived from olefin hydrocarbons when all structural units constituting the resin composition are considered as 100 mol%. Furthermore, it is preferable to form the membrane by bonding the aforementioned layer A and layer B. Here, forming the membrane by bonding layer A and layer B means that layer B is laminated on one or both sides of layer A without any other layer in between; the description of "forming the membrane by bonding one side to another" in the following text also refers to the same method.
[0024] In view of suppressing deformation at high temperatures, it is important that the proportion S of the heat of fusion in the range of 175 to 190°C obtained by differential scanning calorimetry (DSC measurement) is 10% to 70% of the heat of fusion in the range of 30 to 190°C.
[0025] The heat of melt ratio S represents the amount of polyolefin crystals that can remain in the biaxially oriented polyolefin film even at higher temperatures. Considering the above, the lower limit of the heat of melt ratio S is preferably 15%, more preferably 20%, and even more preferably 25%. When the heat of melt ratio S of the biaxially oriented polyolefin film is less than 10%, the amount of crystals required to maintain the structure at high temperatures may be insufficient. Therefore, when the heat of melt ratio S of the biaxially oriented polyolefin film is less than 10%, when used as a release film or process film at high temperatures, the rigidity decreases with increasing thermal shrinkage, inducing excessive embedding and adhesion to the target component. Such excessive embedding and adhesion adversely affect the surface shape of the target component, and peeling the biaxially oriented polyolefin film off the target component may cause damage or deformation. On the other hand, considering the thermal properties of the polyolefin constituting the biaxially oriented polyolefin film, the upper limit of the heat of melt ratio S is 70%, and preferably 50% considering other physical properties. It should be noted that the details of the method for determining the heat of melt ratio S in DSC measurements are described below (the same applies to the heat of melt H described later). It should be noted that the term "object component" here refers to a component laminated to or bonded to the surface of a biaxially oriented polyolefin film when it is used as a release film or process film.
[0026] To ensure that the melting heat ratio S of the biaxially oriented polyolefin film falls within the aforementioned range, methods can be employed that adjust the raw material composition and film-forming conditions to fall within the ranges described later. Regarding the raw material composition, to promote the formation of high-melting-point crystals through film-forming at high temperatures, high-melting-point polyolefins (such as polypropylene) are used as raw materials. The semi-crystallization time and angular frequency ω of the resin constituting the biaxially oriented polyolefin film are appropriately adjusted. 200 This effectively controls the relaxation characteristics. Furthermore, in terms of process, setting the preheating and stretching temperatures for longitudinal and transverse stretching within the range described later, and then introducing a relaxation process after longitudinal and transverse stretching, performing treatment at the temperature and relaxation rate within the range described later, is effective. It should be noted that these methods can also be used in combination appropriately.
[0027] By employing the aforementioned raw material composition and process conditions, stretching and relaxation treatments can be performed under high-temperature conditions. This promotes the relaxation of the amorphous components, which are the main cause of thermal shrinkage stress, and enables the formation of high-melting-point crystals that were previously unattainable for biaxially oriented polyolefin films. As a result, the obtained biaxially oriented polyolefin film can suppress deformation even at high temperatures and can be used even under such conditions.
[0028] From the perspective of suppressing welding under high temperature conditions, the biaxially oriented polyolefin film of the present invention has two layers with different contents of 4-methyl-1-pentene polymer. Among the two layers, when the layer with a relatively low content of 4-methyl-1-pentene polymer is designated as layer A and the layer with a relatively high content of 4-methyl-1-pentene polymer is designated as layer B, layer B is located on at least one surface, and layer B is mainly composed of 4-methyl-1-pentene polymer.
[0029] Here, "the content of 4-methyl-1-pentene polymers is different" means that when comparing the amount (mass%) of 4-methyl-1-pentene polymers contained in the two layers, the difference is greater than 20% by mass. The principal component refers to the component contained in a proportion greater than 50% by mass and less than 100% by mass when all components constituting the layer are considered as 100% by mass. It should be noted that if a layer contains multiple 4-methyl-1-pentene polymers, and their total content exceeds 50% by mass, then 4-methyl-1-pentene polymers are considered the principal component. A 4-methyl-1-pentene polymer is defined as a polymer containing more than 90% by mass and less than 100% by mass of structural units derived from 4-methyl-1-pentene when all structural units constituting the polymer are considered as 100 mol%. It should be noted that, as a method for investigating the content of 4-methyl-1-pentene polymers in a membrane, examples include separating the layers by cutting, separating and quantifying the polymer components by chromatography or solvent extraction using a heated dissolution fractionation apparatus, and then... 13 Methods such as C-NMR calculation of structural units derived from 4-methyl-1-pentene, etc.
[0030] Layer B being located on at least one surface refers to two scenarios: layer B being located on one surface and layer B being located on two surfaces, regardless of the presence of layers other than layers A and B. It should be noted that layer B is responsible for inhibiting welding; considering the effectiveness of this effect on both surfaces, layer B being located on two surfaces is preferred.
[0031] When the biaxially oriented polyolefin film of the present invention has three or more layers, and the content (mass%) of 4-methyl-1-pentene polymer in each layer is completely different, the layer located on the outermost surface with the highest content of 4-methyl-1-pentene polymer is designated as layer B, and the layer with the lowest content of 4-methyl-1-pentene polymer is designated as layer A. However, when there are multiple layers with the lowest content of 4-methyl-1-pentene polymer, the layer with the largest thickness is designated as layer A. Furthermore, when the content of 4-methyl-1-pentene polymer is equal and the highest among the layers on both outermost surfaces, the outermost layers on both sides are designated as layer B.
[0032] In the biaxially oriented polyolefin film of the present invention, from the perspective of heat shrinkage characteristics, the upper limit of the content of 4-methyl-1-pentene polymer in layer A is preferably 10% by mass, more preferably 5% by mass, further preferably 3% by mass, particularly preferably 1% by mass, and most preferably 0% by mass (i.e., not containing 4-methyl-1-pentene polymer). Furthermore, from the perspective of suppressing welding under high-temperature conditions, the content of 4-methyl-1-pentene polymer in layer B is preferably greater than 80% by mass and less than 100% by mass, with a lower limit more preferably 90% by mass, further preferably 95% by mass, particularly preferably 98% by mass, and most preferably 100% by mass (i.e., composed solely of 4-methyl-1-pentene polymer). It should be noted that when layer B exists on both surfaces, its composition can be the same or different. Examples of different compositions of layer B include cases where the content (by mass%) of 4-methyl-1-pentene polymer in the outermost layers on both sides is the highest and equal, but the types of 4-methyl-1-pentene polymer and other resins are different.
[0033] From the perspective of suppressing interlayer delamination that damages the quality of the target component when used as a release film or process film, the unfolded area ratio (Sdr) of at least one surface of the biaxially oriented polyolefin film of the present invention is preferably 0.2 to 10. Here, at least one film surface refers to one or both sides. When the biaxially oriented polyolefin film is used as a release film or process film, it is preferable to laminate the target component on layer B. That is, when layer B exists on one surface, it is preferable that the Sdr of the surface of layer B is within the above range; when layer B exists on two surfaces, the Sdr of one or both sides should be within the above range depending on the surfaces of the target component being laminated.
[0034] Sdr is one of the surface parameters indicating how much the surface area increases due to the uneven structure of the film surface. Generally, a high value is indicated if the surface contains a dense uneven structure. Considering the above, the lower limit of Sdr is more preferably 0.5, and even more preferably 1.0. There is no particular limitation on the upper limit of Sdr, but from the perspective of film-forming properties, it is substantially 10, preferably 5.0. When Sdr is 0.2 or higher, the B layer containing 4-methyl-1-pentene polymers on the surface of the biaxially oriented polyolefin film has a dense uneven structure, which can suppress local surface damage caused by coarse uneven structures. Therefore, when used as a release film, the release properties of the biaxially oriented polyolefin film to the target component and the weld resistance of the biaxially oriented polyolefin film itself are easily maintained even at high temperatures. It should be noted that Sdr can be measured by a known non-contact surface / layer cross-sectional shape measurement system (e.g., the "VertScan" series of Mitsubishi Chemical Co., Ltd. systems, etc.), the details of which are described below.
[0035] To ensure that Sdr is within the aforementioned range, the raw material composition and film-forming conditions must be effective within the ranges described below. In particular, to form a dense, uneven structure in conjunction with stretching in terms of raw materials, the angular frequency ω of the 4-methyl-1-pentene polymer contained in layer B must be optimized. 260 Within an appropriate range (e.g., below 200 rad / s), it is effective to enhance the entanglement of molecular chains and improve the followability during stretching. Furthermore, in terms of process, setting the preheating and stretching temperatures in the stretching process to preferred ranges is effective. It should be noted that these methods can be used in appropriate combinations.
[0036] From the perspective of peeling characteristics at high temperatures, the biaxially oriented polyolefin film of the present invention preferably has a static contact angle I with diiodomethane of at least one film surface of 60 to 90°, and more preferably the surface of layer B satisfies the above condition. Regarding the static contact angle I with diiodomethane, if the outermost surface of the biaxially oriented polyolefin film is uniformly coated with a 4-methyl-1-pentene polymer, it tends to be higher; conversely, if a large amount of polyolefin other than a 4-methyl-1-pentene polymer (e.g., polypropylene) is present in the outermost layer, it tends to be lower. It should be noted that the "static contact angle I with diiodomethane" is sometimes referred to as "contact angle I" below.
[0037] Considering the above aspects, the lower limit of the contact angle I is preferably 60°, more preferably 63°, further preferably 66°, and particularly preferably 69°. The upper limit of the contact angle I is not particularly limited, but considering the raw material characteristics of the 4-methyl-1-pentene polymer and the film-forming properties of the film, 90° is preferred, more preferably 80°. If the contact angle I is 60° or higher, the surface of the biaxially oriented polyolefin film (mainly the B layer surface) is more uniformly coated with the 4-methyl-1-pentene polymer, and defective portions such as excessively dense exposure of polyolefins other than the 4-methyl-1-pentene polymer become very few. Therefore, when the biaxially oriented polyolefin film of the present invention is used as a release film in such a way that the object component is formed on the surface of this layer, the release properties of the object component and the weld resistance of the biaxially oriented polyolefin film itself are easily maintained even at high temperatures.
[0038] To ensure the contact angle I is within the aforementioned range, the layer composition and film-forming conditions must be within the ranges described later. Specifically, this is to ensure the 4-methyl-1-pentene polymer in the surface layer (mainly layer B) is uniformly stretched to achieve its angular frequency ω. 260 The appropriate range being within the preferred range is effective. Additionally, adjusting the thickness of layer B to an appropriate range is also effective. It should be noted that these methods can be used in appropriate combinations.
[0039] From an operability perspective, the sum of the Young's modulus E in the biaxially oriented polyolefin film of the present invention, when the main orientation axis direction is designated as the X direction and the direction orthogonal to the main orientation is designated as the Y direction, is: X+Y The preferred pressure is 5.2~15 GPa. Considering the above aspects, E X+Y The lower limit is more preferably 6.0 GPa. Considering both membrane fabrication properties and heat resistance, E... X+Y The upper limit is preferably 10 GPa. X+Y When the pressure is above 5.2 GPa, the stiffness of biaxially oriented polyolefin film tends to increase, which improves its operability when used as a release film or process film, and enhances its workability and transportability under high temperature environments.
[0040] To improve the E of the biaxially oriented polyolefin film of the present invention X+Y Within the aforementioned range, setting the raw materials and film-forming conditions to the ranges described later is effective. In particular, regarding the raw materials, the melting point and angular frequency ω of the polyolefin resin (e.g., polypropylene resin) other than the 4-methyl-1-pentene polymer contained in layer A are important considerations. 200 Setting the values to appropriate ranges is effective. In terms of process, setting the longitudinal and transverse stretch ratios to appropriate ranges is effective. Additionally, in terms of layer structure, setting the thickness ratio of layer B to the range described later is also effective. It should be noted that these methods can be used in appropriate combinations.
[0041] Here, the main orientation axis direction (X direction) in the biaxially oriented polyolefin film of the present invention refers to the direction with the highest Young's modulus value when the length direction is specified as 0° within the film surface, and the Young's modulus is measured at angles of 0°, 15°, 30°, 45°, 60°, 75°, 90°, 105°, 120°, 135°, 150°, and 165° relative to this length direction at an environment of 30°. It should be noted that when it is unclear which direction is the length direction from the appearance of the biaxially oriented polyolefin film, lines are drawn at 15° intervals using any straight line on the film surface as a reference. Slit-shaped film samples are then sampled parallel to these lines, and the Young's modulus is measured in the same manner to determine the X direction.
[0042] Furthermore, the direction orthogonal to the main orientation (Y direction) on the biaxially oriented polyolefin film of the present invention refers to a direction orthogonal to the main orientation axis direction within the film surface. The Y direction is orthogonal to the X direction determined by the above method within the film surface; if the X direction is determined, it will be automatically determined. It should be noted that the Young's modulus (E) including the X direction... X and Young's modulus in the Y direction (E) Y The details of the method for determining the Young's modulus are described below.
[0043] The biaxially oriented polyolefin film of the present invention, from the perspective of use as a release film and process film in high-temperature environments, preferably has a heat of fusion H in the range of 190°C to 260°C as determined by differential scanning calorimetry (DSC) of 0.1 to 20 J / g. From the above perspective, the lower limit of the heat of fusion H is more preferably 1 J / g, and even more preferably 3 J / g. Similarly, the upper limit of the heat of fusion H is more preferably 15 J / g, and even more preferably 10 J / g. When the heat of fusion H is within the above range, the biaxially oriented polyolefin film contains an appropriate amount of high-melting-point resin (such as 4-methyl-1-pentene polymers) for improving heat resistance and achieving a suitable surface shape. Therefore, when such a biaxially oriented polyolefin film is used as a release film and process film, it maintains high heat shrinkage characteristics while easily maintaining the release properties of the target component and the weld resistance of the biaxially oriented polyolefin film itself, even in high-temperature environments.
[0044] To ensure that the heat of melt (H) of the biaxially oriented polyolefin film of the present invention is within the aforementioned range, it is effective to use raw materials and film-forming conditions within the ranges described later. In particular, setting the proportion of 4-methyl-1-pentene polymers in each layer of the biaxially oriented polyolefin film to an appropriate range is effective. Furthermore, controlling the discharge rate to ensure that the proportion of layer B, containing a large amount of 4-methyl-1-pentene polymer, is within an appropriate range is also effective. It should be noted that these methods can be used in appropriate combinations.
[0045] Considering the thermal shrinkage characteristics under high-temperature conditions, the sum of the shrinkage stress P in the X direction and the Y direction of the biaxially oriented polyolefin film of the present invention at 160°C is... X+Y Preferably, it is -1.0 to 3.0 MPa. Considering the above aspects, P X+Y The upper limit is more preferably 2.0, further preferably 1.5, and particularly preferably 1.0. By making P X+Y When a particle size of 3.0 or below is laminated or covered onto a biaxially oriented polyolefin film, and the film is subjected to high-temperature molding and pressing or oven treatment, the thermal shrinkage of the biaxially oriented polyolefin film can be suppressed. Therefore, the biaxially oriented polyolefin film is less prone to wrinkles, curling, and other deformations, which reduces the transfer of these deformation states to the covered component. On the other hand, for P... X+Y The lower limit is preferably -1.0 from the perspective of the film-forming properties of biaxially oriented polyolefin films; if rigidity at high temperatures is also considered, then 0.0 is preferred. It should be noted that the details of the method for determining the shrinkage stress at 160°C in the TMA measurement are described later.
[0046] In order to make P X+Y Within the aforementioned range, methods can be used to ensure that the raw material composition of the biaxially oriented polyolefin film is within the range described below, as well as the film-forming conditions are within the range described below. In particular, to appropriately control the amorphous relaxation under high-temperature film-forming conditions, melting point and various angular frequencies ω are used. 200 Polyolefin resins within the preferred range described below are effective as polyolefin resin raw materials other than 4-methyl-1-pentene polymers. Furthermore, in terms of process, it is effective to set the preheating and stretching temperatures for longitudinal and transverse stretching to the preferred range described below, and then introduce a relaxation process after longitudinal and transverse stretching, performing the treatment within the preferred temperature and total area relaxation rate range described below. It should be noted that these methods can also be appropriately combined.
[0047] In the biaxially oriented polyolefin membrane of the present invention, the proportion of components with a molecular weight M of 5.0 or less (LogM) as determined by gel permeation chromatography is preferably 30.0 to 39.0% by mass. The upper limit of the proportion of components with LogM of 5.0 or less is more preferably 37.0% by mass, further preferably 36.0% by mass, and particularly preferably 35.0% by mass. The lower limit of the proportion of components with LogM of 5.0 or less is more preferably 31.0% by mass, and further preferably 33.0% by mass.
[0048] Furthermore, the content of components with a molecular weight M of 6.0 or higher (LogM) is preferably 3.0 to 10.0% by mass. The upper limit of the content of components with a LogM of 6.0 or higher is more preferably 8.0% by mass, even more preferably 6.0% by mass, and particularly preferably 5.0% by mass. The lower limit of the content of components with a LogM of 6.0 or higher is more preferably 3.5% by mass, and even more preferably 4.0% by mass.
[0049] When the ratio of components with a molecular weight M of less than 5.0 (LogM) to components with a molecular weight M of 6.0 or higher in the biaxially oriented polyolefin film is within the aforementioned range, the biaxially oriented polyolefin film exhibits appropriate relaxation characteristics, effectively balancing high melting point crystallization and amorphous relaxation during film formation, and readily demonstrating excellent heat resistance. To ensure that the ratio of components with a molecular weight M of less than 5.0 to components with a molecular weight M of 6.0 or higher is within the aforementioned range, it is effective to maintain the raw material composition of the biaxially oriented polyolefin film within the range described later, and also to maintain the film formation conditions within the range described later. In particular, the angular frequency ω of the polyolefin resin other than the 4-methyl-1-pentene polymer used in the A layer is... 200 (Details are described below) Within the preferred range described below, it is effective to adjust the mixing temperature simultaneously during pre-mixing and film formation.
[0050] The biaxially oriented polyolefin film of the present invention, considering heat resistance and other factors, preferably has a melting point Tm1 of 165.0~170.0°C, obtained from the 2nd run of DSC measurement at a heating rate of 20°C / min, where the peak intensity is highest. Considering the above, the lower limit of Tm1 is more preferably 166.0°C, further preferably 166.5°C, and particularly preferably 167.0°C. Furthermore, if the characteristics of the polypropylene resin are considered as described later, the upper limit of Tm1 is 170.0°C. It should be noted that the details of the method for measuring Tm1 are described below.
[0051] Tm1 is an indicator of the melting point of the polyolefin resin, excluding 4-methyl-1-pentene polymers, contained in the biaxially oriented polyolefin film of the present invention. If it is within the above-mentioned range, film can be formed at higher temperatures. Therefore, it is easier to improve heat shrinkage characteristics and is also advantageous in terms of high-melting-point crystal formation, resulting in improved heat resistance of the obtained biaxially oriented polyolefin film. To ensure that Tm1 is within the above-mentioned range, it is effective to make the raw material composition of the biaxially oriented polyolefin film within the range described later, especially by using high-melting-point raw materials, while minimizing the amount of mixtures other than high-melting-point raw materials and increasing the proportion of layer A in the overall biaxially oriented polyolefin film. It should be noted that these methods can be used in combination appropriately.
[0052] The biaxially oriented polyolefin film of the present invention, considering factors such as suppressing welding at high temperatures, preferably has a melting point Tm2 of 200-250°C as observed in the second run of DSC measurement at a heating rate of 20°C / min, measured at 190°C or higher. From the above considerations, a lower limit of Tm2 is more preferably 220°C, and even more preferably 225°C. Furthermore, an upper limit of Tm2 is more preferably 240°C. It should be noted that the details of the method for measuring Tm2 are described below.
[0053] Tm2 is an indicator of the melting point of the 4-methyl-1-pentene polymer contained in the biaxially oriented polyolefin film of the present invention. If it is within the above-mentioned range, both film-forming properties and high-temperature weld resistance can be achieved. To ensure that Tm2 is within the above-mentioned range, it is effective to make the raw material composition of the biaxially oriented polyolefin film within the range described below, particularly by using a 4-methyl-1-pentene polymer with a melting point within an appropriate range and ensuring its addition ratio is within an appropriate range. It should be noted that these methods can be appropriately combined.
[0054] The thickness of the biaxially oriented polyolefin film of the present invention can be appropriately adjusted according to the application and is not particularly limited. From an operational perspective, it is preferably 0.5 to 100 μm. From the above perspective, the thickness of the biaxially oriented polyolefin film is more preferably 1 to 70 μm, and even more preferably 1 to 55 μm. The thickness of the biaxially oriented polyolefin film can be adjusted within a range that does not deteriorate other physical properties by adjusting the screw speed of the extruder, the width of the unstretched sheet, the film forming speed, the stretch ratio, etc. It should be noted that the thickness of the biaxially oriented polyolefin film can be measured using a known micrometer thickness gauge, the details of which are described below.
[0055] Next, the raw materials that can be used in the manufacture of the biaxially oriented polyolefin film of the present invention will be described, but are not limited thereto.
[0056] The biaxially oriented polyolefin film of the present invention comprises two layers with different contents of 4-methyl-1-pentene polymers. The layer with a relatively lower content of 4-methyl-1-pentene polymer is designated as layer A, and the layer with a relatively higher content of 4-methyl-1-pentene polymer is designated as layer B. Furthermore, the content of 4-methyl-1-pentene polymer referred to herein is the content (mass%) of 4-methyl-1-pentene polymer when the entire layer is considered as 100% by mass.
[0057] From the perspective of improving demolding performance and reducing heat shrinkage, the proportion of layer A in the biaxially oriented polyolefin film of the present invention, in terms of thickness, is preferably 70-99.5%. The lower limit of the proportion of layer A is more preferably 80%, further preferably 90%, and particularly preferably 95%. On the other hand, the upper limit of layer A is more preferably 99%, further preferably 98%, and particularly preferably 97%. It should be noted that "in terms of thickness" refers to the proportion of layer A thickness when the overall thickness of the biaxially oriented polyolefin film is considered as 100%. By making the proportion of layer A 70% or more in terms of thickness, heat shrinkage characteristics can be appropriately maintained. On the other hand, by making the proportion of layer A 99.5% or less in terms of thickness, it can be ensured that the thickness of layer B is sufficient to exhibit demolding performance.
[0058] Considering the tensile and thermal shrinkage properties of 4-methyl-1-pentene polymers, the proportion of layer B in the biaxially oriented polyolefin film of the present invention, based on thickness, is preferably 0.5-30%. The lower limit of layer B is more preferably 1%, further preferably 2%, and particularly preferably 3%. The upper limit of layer B is more preferably 20%, further preferably 10%, and particularly preferably 5%. It should be noted that the thicknesses of layers A and B mentioned here refer to the total thickness when multiple layers exist.
[0059] The biaxially oriented polyolefin film of the present invention can also be composited with layers other than A and B, but from the perspective of heat resistance, it is preferred to consist of only A and B layers.
[0060] Considering biaxial tensile strength and heat shrinkage properties, the A layer of the biaxially oriented polyolefin film of the present invention preferably uses polypropylene composition A. In the present invention, polypropylene composition A refers to a composition containing polypropylene resin at a ratio of 90-100% by mass when all components are considered as 100% by mass, and having a melting point of 165.0-170.0°C and an angular frequency ω. 200 A composition having a crystallization rate of 10–70 rad / s and a half-crystallization time of 5–200 seconds, representing the crystallization rate. The lower limit of the amount of polypropylene resin in polypropylene composition A is more preferably 95% by mass, further preferably 97% by mass, particularly preferably 99% by mass, and most preferably 100% by mass, meaning that the constituent components of polypropylene composition A are solely polypropylene resin monomers. It should be noted that when the composition contains multiple components equivalent to polypropylene resin, their total amount exceeds 95% by mass of the total resin, and if the melting point, half-crystallization time, and angular frequency ω... 200 Within the aforementioned range, this corresponds to polypropylene composition A. Furthermore, polypropylene resin refers to a resin that contains propylene units in a proportion greater than 50 mol% and less than 100 mol% when all structural units constituting the resin molecular chain are considered as 100 mol%.
[0061] Considering the heat resistance of the obtained biaxially oriented polyolefin film, the melting point of polypropylene composition A is 165.0~170.0℃. From the above perspective, the lower limit of the melting point of polypropylene composition A is preferably 166.0℃, more preferably 166.5℃, and even more preferably 167.0℃. By setting the melting point of polypropylene composition A to 165.0℃ or higher, high-melting-point crystals are easily formed during film formation at high temperatures, thus improving the heat resistance of the obtained biaxially oriented polyolefin film. It should be noted that the melting points of polypropylene composition A and other components can be determined by DSC, as detailed below. Even when multiple components are included, the temperature with the highest peak intensity in the DSC melting curve is taken as the melting point of polypropylene composition A.
[0062] For polypropylene composition A, considering the heat resistance of the resulting biaxially oriented polyolefin film, an angular frequency ω with a loss tangent of 1, obtained by melt viscoelasticity measurement at 200°C, is preferred. 200 The angular frequency is ω, ranging from 10 to 70 rad / s. 200 It is an indicator of the relaxation properties of the polypropylene composition. This angular frequency ω 200 At low temperatures, the entanglement of molecular chains leads to low relaxation properties (i.e., slow relaxation), but even at high temperatures, the entanglement of molecular chains is easily maintained, which is beneficial for crystallization to a high melting point. On the other hand, the angular frequency ω 200 When the molecular chains are large, there is less entanglement, resulting in high relaxation characteristics (i.e., fast relaxation). This makes it easier to effectively reduce residual strain and relax the amorphous portion during the relaxation process. Considering the above aspects, the angular frequency ω of polypropylene composition A... 200 The lower limit is more preferably 15 rad / s, and even more preferably 20 rad / s. Furthermore, considering the above viewpoint, the angular frequency ω... 200 The upper limit is more preferably 50 rad / s, and even more preferably below 40 rad / s. Angular frequency ω 200 Within the aforementioned range, the relaxation of the amorphous portion of polypropylene composition A and the crystallization to a higher melting point are promoted, which can further improve the heat resistance of the obtained biaxially oriented polyolefin film. It should be noted that the angular frequency ω... 200 It can be measured using a well-known rotating rheometer, the details of which are described later (the angular frequency ω described later). 260 Same here).
[0063] To achieve the angular frequency ω of polypropylene composition A 200 To achieve the aforementioned range, adjusting the molecular weight distribution of the polypropylene resin, which is the main component of polypropylene composition A, to an appropriate range is effective. Furthermore, adjusting the molecular weight distribution of the polypropylene resin under pre-mixing conditions or adding branched polypropylene within an appropriate range is also effective when obtaining polypropylene composition A. It should be noted that these methods can be appropriately combined.
[0064] The semi-crystallization time of polypropylene composition A is preferably 5 to 200 seconds. The upper limit of the semi-crystallization time of polypropylene composition A is more preferably 100 seconds, further preferably 50 seconds, and particularly preferably 30 seconds. When the semi-crystallization time is within the above range, the polypropylene resin component in the composition is prone to recrystallization even during film formation, easily forming high-melting-point crystals. To ensure that the semi-crystallization time of polypropylene composition A is within the above range, it is effective to appropriately adjust the crystallinity and molecular weight distribution of the polypropylene resin constituting polypropylene composition A, and to add branched polypropylene within an appropriate range. The semi-crystallization time is an indicator of the crystallization rate and can be determined by DSC as described later (details are as follows). It should be noted that when polypropylene composition A contains multiple components, the time elapsed at the peak intensity in the DSC melt curve is taken as the semi-crystallization time of polypropylene composition A.
[0065] Polypropylene composition A is preferably composed of a single homopolymer polypropylene resin or a mixture of two or more homopolymer polypropylene resins. Alternatively, as described later, components such as branched polypropylene resins that are useful for controlling crystallization rate, block copolymer polypropylene resins other than homopolymer polypropylene resins, and random copolymer polypropylene resins can be mixed by pre-mixing or the like, without deteriorating the properties. When components other than branched polypropylene resins and homopolymer polypropylene resins are added to polypropylene composition A, their addition amount in the total components of polypropylene composition A is preferably 1.2% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less. It should be noted that, here, homopolymer polypropylene resin refers to a polypropylene resin in which the amount of propylene units is 99.9 to 100 mol% when all structural units constituting the molecular chain of the resin are considered as 100 mol%.
[0066] The polypropylene resin used in polypropylene composition A preferably meets the conditions for homopolymer polypropylene resin A described above. Examples of commercially available resins that meet these conditions include F-704NP and F133A from Polymer Polymer Co., Ltd., HC310BF from Borealis Co., Ltd., and FY6H from Nippon Polypro Co., Ltd. Furthermore, examples of commercially available branched chain polypropylenes that can be added to polypropylene composition A include, for example, "Daploy" WB130HMS, WB135HMS, and WB140HMS from Borealis Co., Ltd., and "WAYMAX" (registered trademark) MFX8, MFX6, and MFX3 from Nippon Polypro Co., Ltd.
[0067] In the biaxially oriented polyolefin film of the present invention, layer B preferably contains the aforementioned 4-methyl-1-pentene polymer in a proportion of 80-100%. The lower limit of the proportion of the 4-methyl-1-pentene polymer in layer B is more preferably 90% or more, further preferably 95% or more, particularly preferably 98% or more, and most preferably 100% by mass. When the proportion of the 4-methyl-1-pentene polymer in layer B is less than 80%, it affects the weld resistance of the obtained biaxially oriented polyolefin film at high temperatures. Furthermore, for purposes such as improving adhesion to other layers, 4-methyl-1-pentene copolymers or the like can be added to layer B.
[0068] The 4-methyl-1-pentene polymer in the biaxially oriented polyolefin film of the present invention, from the viewpoint of forming a structure by stretching, preferably has an angular frequency ω whose loss tangent reaches 1, as determined by melt viscoelasticity measurement at 260°C. 260 The range is 1~500 rad / s. Angular frequency ω 260 The angular frequency at which the loss tangent of molten polypropylene resin reaches 1 is an indicator of the relaxation characteristics of polypropylene resin. The angular frequency ω of 4-methyl-1-pentene polymers... 260 The lower limit is more preferably 5.0 rad / s, and even more preferably 30 rad / s. On the other hand, the angular frequency ω of the 4-methyl-1-pentene polymer... 260 The upper limit is more preferably 200 rad / s, and even more preferably 50 rad / s.
[0069] By adjusting the angular frequency ω of 4-methyl-1-pentene polymers 260 With a tensile strength ranging from 1.0 to 500 rad / s, the molecular chains are difficult to loosen during stretching, thus the tensile stress is easily and evenly transmitted, reducing the formation of coarse uneven structures on the surface or voids and pores in the layer. As a result, the biaxially oriented polyolefin film exhibits excellent heat resistance, such as resistance to weld bonding at high temperatures.
[0070] The melting point of the 4-methyl-1-pentene polymer in the biaxially oriented polyolefin film of the present invention is preferably 200-250°C. The lower limit of the melting point of the 4-methyl-1-pentene polymer is more preferably 210°C, further preferably 220°C, and particularly preferably 225°C. On the other hand, the upper limit of the melting point of the 4-methyl-1-pentene polymer is more preferably 240°C, and further preferably 235°C. When the melting point of the 4-methyl-1-pentene polymer in the biaxially oriented polyolefin film of the present invention is within the above range, it is easy to co-stretch with layers mainly composed of other polyolefins. Furthermore, if the B layer contains such a 4-methyl-1-pentene polymer, when the surface of the B layer comes into contact with the target component at high temperatures, it is easier to suppress the fusion between the two.
[0071] In all resins used in the biaxially oriented polyolefin film of the present invention, various additives may be included, without prejudice to the purpose of the present invention, such as inorganic and organic particles, crystallizing nucleating agents, antioxidants, heat stabilizers, lubricants, antistatic agents, anti-blocking agents, fillers, viscosity modifiers, anti-coloring agents, etc. It should be noted that these components can be used alone or in combination, and can be added to any layer.
[0072] In terms of antioxidant exudation, the selection of the type and amount of antioxidant is important. Specifically, sterically hindered phenolic antioxidants are preferred, and at least one of them is a high molecular weight antioxidant with a molecular weight of 500 or higher. Specific examples include various substances, such as 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (e.g., BASF's "Irganox" 1330: molecular weight 775.2) or tetra[methylene-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane (e.g., BASF's "Irganox" 1010: molecular weight 1177.7), which can be used in combination with 2,6-di-tert-butyl-p-cresol (BHT: molecular weight 220.4). The total content of these antioxidants is preferably in the range of 0.03 to 1.0 parts by weight relative to the total amount of resin constituting the biaxially oriented polyolefin film. If there is too little antioxidant, polymer degradation may occur during the extrusion process, leading to film discoloration and poor long-term heat resistance. If there is too much antioxidant, transparency may decrease due to leaching of these antioxidants. A more preferred content is 0.05 to 0.9 parts by weight, and particularly preferred is 0.1 to 0.8 parts by weight.
[0073] Furthermore, in the raw materials of each layer used in the biaxially oriented polyolefin film of the present invention, a nucleating agent may be added within a range that does not depart from the purpose of the present invention. Examples of nucleating agents used in the biaxially oriented polyolefin film of the present invention include polypropylene α-nucleating agents (dibenzyl sorbitol, sodium benzoate, etc.) and polypropylene β-nucleating agents (potassium 1,2-hydroxystearate, magnesium benzoate, amide compounds such as N,N'-dicyclohexyl-2,6-naphthalenediamide, quinacridone compounds, etc.). However, excessive addition of the above-mentioned other types of nucleating agents can sometimes cause a decrease in tensile strength, void formation, and other effects, resulting in a decrease in transparency and strength. Therefore, when considering the total raw material as 100 parts by weight, it is preferable to set the addition amount to 0.5 parts by weight or less, preferably 0.1 parts by weight or less, and more preferably 0.05 parts by weight or less.
[0074] The biaxially oriented polyolefin film of the present invention is preferably formed into a biaxially stretched film. As a method for biaxial stretching, any one of the following can be used: simultaneous biaxial stretching with blown film, simultaneous biaxial stretching with a tenter frame, and successive biaxial stretching with a tenter frame. Among these, considering the control of film formation stability, thickness uniformity, film rigidity, and dimensional stability, the successive biaxial stretching with a tenter frame is preferred.
[0075] Next, an embodiment of the method for manufacturing the biaxially oriented polyolefin film of the present invention will be described using a layer structure of layer B / layer A / layer B as an example, but it is not limited thereto.
[0076] First, considering the total resin as 100% by mass, 99.7% by mass of homopolymer polypropylene resin and 0.3% by mass of branched polypropylene resin are dry-mixed and fed into a twin-screw extruder set at 240-280°C. After melt mixing, the mixture is cooled to obtain granules for layer A of polypropylene composition A. The granules for layer A obtained through the above steps are fed into a single-screw extruder. 96.0% by mass of 4-methyl-1-pentene polymer and 4.0% by mass of 4-methyl-1-pentene-propylene copolymer (here, the mass percentage values are the mass ratio when the total resin is considered as 100% by mass) for layer B are pre-mixed in granular form and fed into another single-screw extruder. Melt extrusion is performed at a temperature preferably 200-290°C, more preferably 240-280°C, and even more preferably 260-280°C. Then, after removing foreign matter and degraded polymer using a filter installed in the polymer pipeline, the layers are laminated into a B / A / B layer structure using a multi-manifold type composite T-die, and discharged onto a casting drum for cooling and curing, thereby obtaining a laminated unstretched sheet with a B / A / B layer structure. At this point, for the lamination thickness ratio, the total thickness of the B layers is preferably 0.5% to 30% (based on thickness). The lower limit for the B layers is more preferably 1%, further preferably 2%, and particularly preferably 3%. The upper limit for the B layers is more preferably 20%, further preferably 10%, and particularly preferably 5%. It should be noted that the thicknesses of the B layers on both sides can be the same or different.
[0077] Furthermore, the surface temperature of the casting drum is preferably 20~100°C, more preferably 30~90°C, and even more preferably 40~80°C. When the casting temperature is within the above range, the formation of low-melting-point β-crystals in the polypropylene resin crystals can be suppressed, which facilitates an increase in the proportion of high-melting-point crystals in the film. As a method for sealing the casting drum, any one of the following can be used: electrostatic application, sealing using the surface tension of water, air knife method, pressure roller method, underwater casting method, etc. The air knife method, which allows for easy control of surface roughness, is preferred. When using the air knife method, the air temperature of the air knife is preferably 20~100°C, and the blowing air speed is preferably 130~150 m / s. In addition, to avoid vibration of the laminated unstretched sheet, it is preferable to appropriately adjust the position of the air knife so that the air flows in the downstream direction of film formation.
[0078] The resulting laminated unstretched sheet is then introduced into a longitudinal stretching (stretching along the length direction) process. In the longitudinal stretching process, the laminated unstretched sheet is preheated before stretching using heated metal rollers at 150–160°C, preferably 152–159°C, and more preferably 154–158°C. If the preheating temperature is within the above range, the laminated unstretched sheet is introduced into the longitudinal stretching process in a softened state, allowing for stretching without applying excessive stress during the process, thus easily reducing thermal shrinkage stress. Furthermore, it also reduces the amount of low-melting-point β-crystals in the laminated unstretched sheet and facilitates an increase in the proportion of high-melting-point crystals in the film.
[0079] Then, the film is stretched along its length by 3.8 to 6.0 times between rollers with a preheated circumferential speed difference, to obtain a longitudinally uniaxially stretched film. This stretching ratio is preferably 4.0 to 5.5 times, more preferably 4.2 to 4.8 times. The stretching temperature is above 150°C and below 160°C, preferably 152 to 158°C, more preferably 154 to 158°C. If the stretching temperature is within the above range, it is possible to maintain the stretching conformability of the 4-methyl-1-pentene polymer contained in layer B while suppressing excessive strain residue of the polypropylene resin contained in layer A, and to pull molecular chains from softened crystals. Combined with the subsequent relaxation process, this promotes crystallization to a high melting point.
[0080] At the end of the longitudinal stretching process, the longitudinally uniaxially stretched film is brought into contact with a metal roller having a circumferential speed difference and maintained at 140-160°C, and relaxed along its length at a relaxation rate greater than 0% and less than 10%, and then cooled to room temperature. The relaxation temperature is preferably 142-160°C, more preferably 145-160°C, further preferably 150-160°C, and particularly preferably 154-160°C. When the relaxation temperature is within the above range, longitudinal stretching promotes the rearrangement of molecular chains pulled from the crystals in the polypropylene resin contained in layer A, and crystals with higher melting points can be formed. Furthermore, the relaxation rate in the longitudinal stretching process is preferably 0.1-10%, more preferably 1.0-10%, further preferably 3.0-10%, and particularly preferably 5.0-10%. By keeping the relaxation rate in the longitudinal stretching process within the above range, the tension of the molecular chains of the polypropylene resin contained in layer A is easily eliminated. As a result, in addition to promoting amorphous relaxation and reducing shrinkage stress, it is also easy to promote the rearrangement of molecular chains.
[0081] Next, the longitudinally uniaxially stretched film is fed into a tenter frame, preheated by clamping its two ends in the width direction, and then stretched laterally in the width direction to 7.0 to 13 times its original length (transverse stretching process). The temperature in the preheating process before stretching is 170 to 190°C, preferably 173 to 185°C, more preferably 175 to 185°C, and even more preferably 177 to 185°C. If the preheating temperature is within the above range, it can promote the structural deformation of the 4-methyl-1-pentene polymer contained in layer B, and the transverse stretching process can be carried out in a state where the polypropylene resin contained in layer A has softened the crystals formed in the longitudinal stretching process. This allows for stretching without applying excessive stress in the transverse stretching process, and the heat shrinkage stress is easily reduced.
[0082] Furthermore, the stretching temperature in the transverse stretching process after the preheating step exceeds 170°C but is below 180°C, preferably 173~180°C, and more preferably 175~180°C. If the transverse stretching temperature is within this range, it can promote the structural deformation of the 4-methyl-1-pentene polymer contained in layer B and suppress excessive strain residue of the polypropylene resin contained in layer A, while simultaneously allowing molecular chains to be drawn from the crystals softened by preheating. Therefore, in conjunction with the subsequent relaxation step, it promotes crystallization to a high melting point.
[0083] In the subsequent relaxation process after transverse stretching, while the crystal is held at a moderately tight clamp in the width direction, relaxation is performed at a relaxation rate of preferably 10-20%, more preferably 11-18%, and even more preferably 12-15%. By keeping the relaxation rate after transverse stretching within the above range, the tension of the molecular chains is easily eliminated. Therefore, in addition to promoting amorphous relaxation and reducing shrinkage stress, the mobility of the molecular chains reaches an appropriate range, which also facilitates the rearrangement of the molecular chains. Moreover, the heat-fixing temperature at this time is preferably above 170°C and below 190°C, preferably 173-185°C, and more preferably 175-185°C. If the relaxation temperature is within the above range, the rearrangement of the molecular chains pulled from the crystal is promoted by transverse stretching, and a high-melting-point crystal with a thicker lamellar thickness can be formed.
[0084] Furthermore, the biaxially oriented polyolefin film of the present invention includes a relaxation process in both the longitudinal stretching process and the transverse stretching process. The total area relaxation rate (%) calculated from each stretching ratio and relaxation rate in the longitudinal stretching process and the transverse stretching process is preferably 10-30%, more preferably 13-25%, and even more preferably 15-20%. The total area relaxation rate (%) is calculated by the following formula. If it is within the above range, amorphous relaxation is easier to perform, and the shrinkage stress of the biaxially oriented polyolefin film as a whole is easier to reduce.
[0085] Total area relaxation rate (%) = [1 - (1 - relaxation rate of longitudinal stretching process / 100) × (1 - relaxation rate of transverse stretching process / 100)] × 100
[0086] Then, while the film is held in the width direction by clamps, it is cooled at 80~130℃, guided to the outside of the tenter frame, the clamps at the film ends are released, the film edge is cut off in the winding process, and the film product roll is wound up.
[0087] The biaxially oriented polyolefin film obtained above can be used for various applications such as packaging film, surface protection film, process film, battery film, hygiene products, agricultural products, building materials, and medical products. In particular, due to its excellent heat resistance, it is preferred as a process film that requires high-temperature treatment in the drying of coating materials and the molding of thermosetting resins, as well as a release film, a substrate film for current collector foil in secondary batteries, and a packaging film for retort filling. It is especially preferred as a release film for use in high-temperature areas (details of the applications are described below).
[0088] The release film and process film of the present invention will be described below. The release film and process film of the present invention include the biaxially oriented polyolefin film of the present invention. Here, "including the biaxially oriented polyolefin film of the present invention" refers to two cases: either the film is formed solely from the biaxially oriented polyolefin film of the present invention, or other layers are provided on the biaxially oriented polyolefin film of the present invention. In the present invention, the release film refers to a film that functions as follows: it is adhered to a molded body, film, or other object, protecting the object from damage and contamination during processing and handling, and can be easily peeled off and discarded when used as a final product. Furthermore, the process film refers to a film used in the manufacturing process of a molded body, film, or other object. Examples include films that are adhered to an object during manufacturing to protect it from damage and contamination, and films that function as a support when it is difficult to form a film on a thin or brittle object.
[0089] The release film of the present invention is particularly preferred for use in the curing of fiber-reinforced composite materials, substrates, or molds due to its excellent heat resistance and release properties. These applications are all equivalent to release applications in high-temperature areas. For fiber-reinforced composite materials, it refers to its use by bonding to raw materials formed by reinforcing resin with glass fibers or carbon fibers. For substrates, it refers to its use by bonding to a board (substrate) used to configure components that perform a certain function; examples of substrates include printed circuit boards and glass substrates used in electronic circuit boards, displays, etc. For molds, it refers to its use by bonding to articles (molded articles) processed in the molding process of protecting semiconductor components or integrated circuits (ICs) with semiconductor packaging. Since the processing of fiber-reinforced composite materials, substrates, and molded articles involves high-temperature heating, the release film of the present invention, with its excellent release properties in high-temperature environments, is suitable for protecting these components.
[0090] The laminate of the present invention will now be described. The biaxially oriented polyolefin film of the present invention, due to its excellent heat resistance and release properties, is preferably used when forming a laminate with a metal film or a transparent conductive film by vapor deposition or sputtering of the biaxially oriented polyolefin film of the present invention. Specifically, as one embodiment of the laminate of the present invention, a laminate formed by contacting at least one side of the metal film with the biaxially oriented polyolefin film of the present invention can be cited.
[0091] In vapor deposition and sputtering processes, polyethylene terephthalate (PET) films, with their excellent properties, are often used due to their heat resistance and rigidity. However, because PET has ester bonds and high hydrophilicity, PET films contain trace amounts of moisture. This trace amount of moisture can sometimes cause adverse effects during vapor deposition and sputtering processes, especially when vapor deposition is performed on metals belonging to Group 1 or 2 of the periodic table, or compounds containing these metals. Against this background, considering the possibility of obtaining a suitable laminate even when the presence of trace amounts of moisture makes it difficult to use PET films, when the laminate of the present invention has a metal film, it is preferable that the metal film contains a metal belonging to Group 1 or 2 of the periodic table. Here, metals belonging to Group 1 or 2 refer to lithium, sodium, potassium, rubidium, cesium, francium, beryllium, magnesium, calcium, strontium, barium, and radium.
[0092] Furthermore, under high-temperature conditions, moisture in the membrane evaporates as escaping gas, and its impact becomes significant, especially under high-vacuum conditions such as metal vapor deposition processes. If gas is released from the membrane, the vacuum level within the system may deteriorate, reducing the quality of the metal film formed by vapor deposition and decreasing the yield of the vapor deposition process. Considering the above aspects, the biaxially oriented polyolefin membrane of the present invention, which has less moisture than PET film, is suitable for forming metal films, and the laminate of the present invention can maintain good film quality in the metal film.
[0093] Furthermore, electrolyte membranes used in fuel cells, semi-solid-state batteries, and all-solid-state batteries are typically manufactured under strictly controlled temperature and humidity conditions. In particular, sulfide-type electrolyte membranes react with moisture to produce hydrogen sulfide; therefore, the process membranes used in their manufacture also require extremely low moisture content. Therefore, the biaxially oriented polyolefin membrane of the present invention is preferably used as the process membrane in manufacturing such electrolyte membranes. That is, as a preferred embodiment of the laminate of the present invention, a laminate formed by contacting at least one side of the electrolyte membrane and the biaxially oriented polyolefin membrane can also be cited. Furthermore, a laminate for use in fuel cells, semi-solid-state batteries, or all-solid-state batteries is particularly preferred.
[0094] Considering the above aspects, the upper limit of the water content of the biaxially oriented polyolefin film of the present invention is preferably 2000 ppm, more preferably 1000 ppm, further preferably 500 ppm, particularly preferably 200 ppm, and most preferably 100 ppm. The lower limit of the water content is not particularly limited and is essentially 1 ppm. It should be noted that the water content of the biaxially oriented polyolefin film can be determined by the Karl Fischer method, the details of which are described below.
[0095] To ensure that the water content of the biaxially oriented polyolefin film of the present invention falls within the aforementioned range, it is preferable to minimize the content of hydrophilic resin in the biaxially oriented polyolefin film and to minimize the amount of additives to the required minimum. Specifically, in all components of the biaxially oriented polyolefin film of the present invention, it is preferable to set the lower limit of the content of polyolefin resins such as polypropylene resin to 90% by mass, more preferably 95% by mass, and even more preferably 97% by mass. It should be noted that the upper limit of the content of these resins is substantially 100% by mass.
[0096] Considering the above aspects, when all the resin components of the biaxially oriented polyolefin film of the present invention are considered as 100 parts by weight, the content of antioxidant is preferably 0.05 to 0.9 parts by weight, more preferably 0.1 to 0.8 parts by weight. Since phosphorus antioxidants that ooze to the surface can sometimes reduce the characteristics and quality of the metal film formed on the surface, it is preferable to control their content. More specifically, in all the components of the biaxially oriented polyolefin film of the present invention, the content of phosphorus antioxidants is preferably 0.01 parts by weight or less, more preferably 0.005 parts by weight or less (ppm), and even more preferably 0.001 parts by weight or less. There is no particular limitation on the lower limit of the content of phosphorus antioxidants; theoretically, it is 0 parts by weight (i.e., a substance without phosphorus antioxidants). It should be noted that, regarding the content of antioxidants containing phosphorus antioxidants, considering characteristics, quality, and reducing adverse effects, it is preferable to set the same setting even when the film formed on the surface is not a metal film.
[0097] From the perspective of mitigating adverse effects caused by exudation in the biaxially oriented polyolefin film of the present invention, the total content of additives other than antioxidants (e.g., antistatic agents, viscosity modifiers, anti-coloring agents, lubricants, etc.) is preferably 0 to 0.05 parts by weight. A content of 0 parts by weight of these additives is synonymous with the absence of these additives.
[0098] As described above, the biaxially oriented polyolefin film of the present invention has extremely low water content and releases very little gas. Furthermore, it exhibits superior heat resistance and operability compared to existing polyolefin films. Therefore, it is preferred for use in forming transparent conductive films requiring more stringent processing conditions and heat resistance. Specifically, as a preferred embodiment of the laminate of the present invention, a laminate formed by contacting at least one side of the transparent conductive film with the biaxially oriented polyolefin film of the present invention can also be cited. Here, a transparent conductive film refers to a thin film formed from a material that is conductive and transmits visible light; specific examples include indium tin oxide (ITO), zinc oxide (ZnO), and palladium films.
[0099] Next, the current collector of the present invention will be described. The current collector of the present invention is formed using the biaxially oriented polyolefin film of the present invention. The biaxially oriented polyolefin film of the present invention is preferred as a current collector due to its excellent heat resistance. A current collector refers to a foil-like laminate used in the electrodes of a battery such as a lithium-ion battery. Generally, metal foil is used as a current collector, but to improve safety and weight reduction, laminates formed by laminating a metal film onto a resin film as a substrate are also used. This metal film is laminated, for example, by processes such as vapor deposition, sputtering, plating, or electroless plating. Furthermore, from the perspective of increasing the energy density of the battery, a small film thickness is required for the substrate of the current collector; however, on the other hand, if the film becomes thinner, its rigidity decreases, thus significantly reducing the operability during processing. Especially in the process of laminating the metal film, high temperatures such as radiant heat are applied during processing, and tension is also applied in the transport direction, thus requiring the film to have good operability. The biaxially oriented polyolefin film of the present invention can be thinned and has good operability, therefore it is preferred for use as a current collector.
[0100] Next, the storage battery of the present invention will be described. The storage battery of the present invention is formed using the biaxially oriented polyolefin film of the present invention. Due to its excellent heat resistance, the biaxially oriented polyolefin film of the present invention is preferably used as a current collector, and is generally used in storage batteries where the current collector is used as an electrode. A storage battery is a device that pre-stores electrical energy and restores it to electrical energy for use when needed. Specific examples include lead-acid batteries, nickel-metal hydride batteries, lithium-ion batteries, NAS batteries, and redox flow batteries.
[0101] Example
[0102] The present invention will now be described in detail through examples. It should be noted that the characteristics are measured and evaluated using the following methods.
[0103] (1) Film thickness
[0104] The thickness of the membrane was measured using a micrometer thickness gauge (manufactured by Anritsu Corporation). Five 10cm square samples were taken from the membrane, and the average value was calculated. This average value was taken as the membrane thickness.
[0105] (2) The ratio of heat of fusion S at 175~190℃ and heat of fusion H at 190~260℃
[0106] Using a differential scanning calorimeter (Thermo plus EV02DSCvesta, manufactured by Rigaku Corporation), a melting curve was obtained by heating 3 mg of biaxially oriented polyolefin film from 25 °C to 260 °C at a rate of 20 °C / min in a nitrogen atmosphere.
[0107] The proportion of heat of fusion of <175~190℃ S>
[0108] For the obtained melt curve, a straight baseline is established within the range of 30~190℃. The heat of fusion is calculated from the area enclosed by the straight baseline and the melt curve, and then converted into heat per unit mass of sample to calculate the heat of fusion (J / g) for 30~190℃. Additionally, within the range of 175~190℃, the heat of fusion is calculated from the area enclosed by the straight baseline and the melt curve, and then converted into heat per unit mass of sample to calculate the heat of fusion (J / g) for 175~190℃. Substituting the obtained heats of fusion for 30~190℃ and 175~190℃ into the following formula, the proportion S (%) of the heat of fusion for 175~190℃ is obtained.
[0109] The proportion of heat of fusion at 175~190℃, S (%) = [Heat of fusion at 175~190℃] × 100 / [Heat of fusion at 30~190℃]
[0110] <Heat of fusion H> at 190~260℃
[0111] For the above melting curve, a straight baseline is set in the range of 190~260℃. The heat of fusion is calculated from the area enclosed by the straight baseline and the melting curve. This heat is then converted into the heat per unit mass of the sample, and the heat of fusion H (J / g) at 190~260℃ is calculated.
[0112] (3) The unfolded area ratio Sdr
[0113] The measurements were performed using a scanning white interference microscope "VS1540" (manufactured by Hitachi Hitachi Systems Co., Ltd., with measurement conditions and apparatus configuration described below). Multiple field-of-view measurements of 561.1 μm × 561.5 μm were performed for each field of view, with each field of view consisting of 5 × 5 fields. All images were then stitched together with a 20% overlap to obtain surface shape data of 2356.716 μm × 2358.294 μm. The accompanying analysis software was used to complete the image processing (full completion), and surface correction was performed using a fourth-order polynomial approximation. The surface shape was then determined by applying a median filter (3 × 3 pixels). During the measurements, the intersection of the diagonals of a 5 cm × 5 cm square biaxially oriented polyolefin film was used as the starting point. A total of three measurement locations were determined following the steps described above, and measurements were performed at each location. The unfolded area ratio Sdr for each measurement location was calculated, and the average value was taken. It should be noted that the above measurements were performed on both sides of the membrane.
[0114] <Method for determining the measurement location>
[0115] Measurement 1: Determine the position of the starting point.
[0116] Measurement 2: 10.0 mm to the right of the measurement starting point.
[0117] Measurement 3: Position 10.0 mm to the left of the measurement starting point.
[0118] <Measurement conditions and apparatus configuration>
[0119] Objective lens: 10x
[0120] Lens tube: 1x
[0121] Zoom lens: 1x
[0122] Wavelength filter: 530nm white
[0123] Measurement mode: Wave
[0124] Measurement software: VS-Measure 10.0.4.0
[0125] Analysis software: VS-Viewer 10.0.3.0
[0126] Measurement area: 561.1 μm × 561.5 μm
[0127] Pixel count: 1,024 × 1,024
[0128] Device Name: VertScan 2.0 R5300GL-Lite-AC manufactured by Ryukyu Corporation (registered trademark)
[0129] Measurement conditions: SONY HR-57 1 / 2 inch CCD camera
[0130] Objective lens: 10x
[0131] Intermediate lens: 0.5 x
[0132] Wavelength filter: 530nm white
[0133] Measurement mode: Wave
[0134] Measurement software: VS-Measure Version 5.5.1
[0135] Analysis software: VS-Viewer Version 5.5.1
[0136] Measurement area: 561.097 μm × 561.473 μm
[0137] (4) Contact angle of diiodomethane I
[0138] Using diiodomethane (methylene iodide) as the test solution, and a contact angle meter CA-D manufactured by Kyowa Interface Chemicals Co., Ltd., the static contact angle relative to the membrane surface was determined and taken as contact angle I. Measurements were performed at three locations within a 5cm × 5cm membrane, and the average value was taken. Contact angle I was measured 30 seconds after the liquid was dropped onto the membrane surface. It should be noted that the above measurements were performed on both sides of the membrane.
[0139] (5) Young's modulus E X+Y
[0140] Five rectangular pieces (150 mm x 10 mm in length, measured in the direction of measurement) of biaxially oriented polyolefin film were cut from each rectangular piece as samples. The measurement direction was arbitrarily chosen and defined as the 0° direction. Tensile testing was then performed using an Original Technic TENSILON (registered trademark) UCT-100 machine at 23°C and 65% relative humidity. The initial chuck distance was set to 50 mm and the tensile speed to 300 mm / min. Young's modulus was calculated according to the method specified in JIS K7161 (2014). Five measurements were taken for each sample, and the average value was used as the tensile strength and Young's modulus of that sample. Then, Young's modulus was measured within the film surface at angles from 0° to 175° at 5° intervals relative to the measurement direction. The direction showing the highest value was designated as the main orientation direction (X direction), and the direction orthogonal to it was designated as the direction orthogonal to the main orientation (Y direction). The experiment was conducted 5 times, and the average value was calculated. The Young's modulus in the X direction was taken as EX, and the Young's modulus in the Y direction was taken as EY. The sum of these values was taken as E. X+Y .
[0141] (6) Shrinkage stress P at 160℃ X+Y
[0142] Using a thermomechanical analysis apparatus (SII Nanoteknologi Co., Ltd. / Model TMA / SS6100), thermal shrinkage stress curves in the measurement directions (X and Y directions) were obtained under the following conditions. The X and Y directions were determined by the method described in (5).
[0143] (a) Sample: 4mm wide × 20mm long
[0144] (b) Initial load: 0.0 mN
[0145] (c) Temperature program: Increase the temperature from 30°C to 200°C at a rate of 10°C / min.
[0146] (d) Construction of the heat shrinkage stress curve: Divide the observed load (N) at each temperature by the cross-sectional area (thickness × sample width) of the biaxially oriented polyolefin film to calculate the shrinkage stress (MPa) at each temperature, and construct a temperature-shrinkage stress curve (heat shrinkage stress curve). The shrinkage stress (MPa) at 160℃ is read from the above heat shrinkage stress curve. Measurements are performed three times in each direction, and the average value is calculated. The value in the X direction is taken as PX, the value in the Y direction as PY, and the sum of PX and PY is taken as P. X+Y .
[0147] (7) Melting point of raw materials and Tm1 and Tm2 of biaxially oriented polyolefin film
[0148] A 5 mg sample was collected in an aluminum dish and measured using a differential scanning calorimeter (Thermo plus EV02 DSCvesta, manufactured by Rigaku Corporation) under a nitrogen atmosphere. For the raw material, the temperature was first increased from 30°C to 260°C at a rate of 20°C / min, and then held at 260°C for 5 minutes. Next, the temperature was decreased from 260°C to 30°C at a rate of 20°C / min, and then increased again from 30°C to 260°C at a rate of 20°C / min. The highest peak temperature observed in the melt curve at this point was taken as the melting point of the raw material. Similarly, measurements were performed on the biaxially oriented polyolefin film. The highest peak temperature within the range of 30–190°C was identified as the melting point of the polypropylene resin in the biaxially oriented polyolefin film, i.e., Tm1 (°C). The highest peak temperature within the range of 190–260°C was identified as Tm2, the melting point of the 4-methyl-1-pentene polymer in the biaxially oriented polyolefin film. It should be noted that when the polyolefin composition is a polyolefin composition using multiple resin components without prior mixing, the resin composition collected by melt extrusion of only layer A is measured, or only layer A is collected from unstretched sheet or stretched film for measurement.
[0149] (8) Half-crystallization time
[0150] Using a differential scanning calorimeter (Thermo plus EV02DSCvesta, manufactured by Rigaku Corporation), 3 mg of polypropylene resin or a polypropylene composition was heated from 25°C to 250°C at a rate of 20°C / min under a nitrogen atmosphere and held for 5 minutes. Then, the temperature was decreased from 250°C to 130°C at a rate of 20°C / min and held at 130°C for 30 minutes. The time it takes for the sample temperature to reach 130°C is considered 0 seconds. For the endothermic curve obtained during this isothermal holding at 130°C, the time it takes for the maximum intensity peak to appear is defined as the half-crystallization time (seconds). It should be noted that when using multiple resin components as the polyolefin composition without pre-mixing, measurements are performed on resin compositions collected only from the melt extrusion of layer A, or on layers A collected only from unstretched sheets or stretched films.
[0151] (9) Angular frequency ω 200 angular frequency ω 260
[0152] In the rotational rheometer (アントンパール The measurements were performed using a 25mm diameter cone plate mounted on a Japanese MCR302 substrate. A polypropylene composition (or polypropylene resin and polyolefin resin) was placed on a plate heated to 200°C or 260°C and allowed to stand for 10 minutes under a nitrogen atmosphere. Then, while maintaining the above temperature, viscoelasticity was measured by varying the angular frequency from 0.5 rad / s to 500 rad / s under a 5% strain. Based on the obtained curve of angular frequency versus loss tangent, the angular frequency at which the loss tangent reaches 1 was designated as ω. 200 (rad / s), the angular frequency obtained by measurement at 260℃ is set as ω. 260 (rad / s). It should be noted that, when using multiple resin components as a polyolefin composition without pre-mixing, the determination is performed on the resin composition collected by melt extrusion of only layer A, or on the determination of only layer A collected from unstretched sheet or stretched film.
[0153] (10) The proportion of components with a molecular weight M of less than 5.0 (LogM) and the proportion of components with a molecular weight M of more than 6.0 (LogM).
[0154] Using 1,2,4-trichlorobenzene as a solvent, the mixture was stirred at 165°C for 30 minutes to dissolve the biaxially oriented polyolefin membrane. The solution was then filtered using a 0.5 μm filter, and the molecular weight distribution of the filtrate was determined by gel permeation chromatography (GPC). The proportions of components with a molecular weight M of less than 5.0 (LogM) and components with a molecular weight M of 6.0 or higher were calculated from the integral curve of the obtained molecular weight distribution. It should be noted that the determination based on gel permeation chromatography (GPC) was performed using the apparatus and conditions described below.
[0155] <Apparatus and Measurement Conditions>
[0156] Equipment: Agilent Technologies PL-GPC220 high-temperature GPC unit
[0157] Detector: Differential refractive index detector (RI detector) manufactured by Agilent Technologies.
[0158] Columns: Agilent PL1110-6200 (20 μm MIXED-A) × 2
[0159] Flow rate: 1.0 mL / min
[0160] Column temperature: 145℃
[0161] Injection volume: 0.500 mL
[0162] Sample concentration: 0.1 wt%
[0163] Standard samples: Monodisperse polystyrene manufactured by Tokyo Soy Corporation, and bibenzyl polystyrene manufactured by Tokyo Chemical Industry Co., Ltd.
[0164] (11) Moisture content
[0165] Samples of biaxially oriented polyolefin or PET films were placed in a room conditioned to 23°C and 20% relative humidity for at least 4 hours, and then immersed in distilled water at 23°C for 24 hours. Afterward, the surface moisture was wiped off, and the moisture in the samples was dried and vaporized using a micro-moisture analyzer (Mitsubishi Chemical Co., Ltd., CA-20 model) at 150°C. The moisture content was then quantified using the Karl Fischer method to calculate the water content.
[0166] (12) Evaluation of heat resistance properties
[0167] After cutting thick paper (manufactured by Daio Paper Corporation, product number C-55) into 10cm squares, interlock the biaxially oriented polyolefin film or PET film, which has been cut into 15cm squares. Figure 1The paper is then placed on both sides of the thick paper along with a 20cm square SUS board. A hot press is used to heat and pressurize the paper for 5 minutes each at 1.0 MPa and temperatures of 175°C, 180°C, and 185°C. Afterward, it is removed from the press and cooled to room temperature. Then, the biaxially oriented polyolefin film or PET film that has overflowed from the thick paper is peeled off from each other, and the thick paper is then peeled off from the biaxially oriented polyolefin film or PET film. It should be noted that... Figure 1 The symbols 1-4 in the diagram represent, respectively, the SUS plate, the test film, the thick paper, and the direction of pressure. The shape stability and high-temperature peel resistance of the thick paper and biaxially oriented polyolefin film or PET film after treatment or peeling at various temperatures are evaluated visually according to the following standards. Regarding the evaluation, all evaluation items are initially performed at a heating temperature of 175°C; only qualified evaluation items are evaluated at a heating temperature of 180°C. Furthermore, only items that pass the evaluation at 180°C are evaluated at a heating temperature of 185°C.
[0168] (shape stability)
[0169] Paper that has no observed bends or creases is considered acceptable; paper that has at least one of the following bends or creases is considered unacceptable. The evaluation criteria are as follows.
[0170] (High-temperature peel resistance)
[0171] After pressure treatment, the biaxially oriented polyolefin film or PET film overflowing from the thick paper can be peeled off at the interface between the films. When the film peeled off from the thick paper does not remain on the thick paper, it is evaluated as qualified. When it cannot be peeled off or even if it can be peeled off, some film remains on the thick paper, it is evaluated as unqualified. The evaluation shall be carried out according to the following standards.
[0172] <Evaluation Criteria (General for Shape Stability and High-Temperature Peel Resistance)>
[0173] For shape stability and high-temperature peel resistance, the following criteria shall be used for evaluation. If each property is rated A to C, it shall be evaluated as having heat resistance.
[0174] A: Qualified at 175℃, 180℃, and 185℃.
[0175] B: Passes at 175℃ and 180℃, but fails at 185℃.
[0176] C: Passes at 175℃, but fails at 180℃.
[0177] D: Not up to standard at 175℃.
[0178] (13) Interlayer tightness
[0179] The biaxially oriented polyolefin film of the present invention was cut into pieces with a width of 25 mm in the main orientation (X) direction and a length of 70 mm in the direction perpendicular to the main orientation (Y). An 80 mm acrylic polyester adhesive tape (Nitto Denko Corporation, Nitto 31B tape, 19 mm wide) was applied to the film with the two ends aligned in the length direction. A tape-laminated laminate sample was prepared by rolling the film once with a 2 kgf roller and then allowing it to stand for 24 hours at 25°C and 55% ± 5% humidity. Then, the tape-laminated laminate sample was applied to the opposite side of a 1.5 mm thick SUS plate with double-sided tape (Nitto Denko No. 532 tape, 0.08 mm thick). The SUS plate was then fixed to an Autograph (registered trademark) AG-1S universal testing machine manufactured by Shimadzu Corporation using a pneumatic chuck. Next, a 5mm section of adhesive tape was peeled off from the bonding end and fixed with a pneumatic chuck. The peel force (N / 19mm) was measured when peeling at a peel angle of 180° and a tensile speed of 300mm / min. The average peel force for 10-40mm was calculated from the graph of the measured peel force (N / 19mm) versus the test length (mm), and evaluated according to the following criteria.
[0180] A: The average peel strength is above 2.0 N / 19 mm, and the standard deviation of the peel strength is less than 10% of the average value.
[0181] B: The average peel strength is above 2.0 N / 19 mm, and the standard deviation of the peel strength is above 10% and less than 20% of the average value.
[0182] C: The average peel strength is above 2.0 N / 19 mm, and the standard deviation of the peel strength is above 20% of the average value.
[0183] D: Peel strength less than 2.0 N / 19 mm, or the standard deviation of peel strength is more than 20% of the average value.
[0184] (14) High-temperature transportability
[0185] A 500mm wide biaxially oriented polyolefin film was fed into a drying oven at 140°C and conveyed for 20 seconds under a conveying tension of 1.0MPa. It was then wound into a 200m roll with a winding tension of 200N / m. Next, only 1m of the 500mm wide biaxially oriented polyolefin film was wound. Under free tension (the state where the biaxially oriented polyolefin film hangs vertically due to its own weight), and under tensions of 1kg / m and 3kg / m uniformly applied across the entire width of the biaxially oriented polyolefin film, the presence of wrinkles, dents, or other defects in flatness was visually inspected. Evaluation was conducted according to the following standards.
[0186] A: There are no areas with poor planarity under free tension.
[0187] B: Areas with poor planarity were observed under free tension, but these areas disappeared under a width tension of 1 kg / m.
[0188] C: Areas with poor flatness were observed under a width tension of 1 kg / m, but these areas disappeared under a width tension of 3 kg / m.
[0189] D: Even under a width tension of 3 kg / m, areas with poor planarity were observed.
[0190] (15) Evaluation of yield during metal film formation
[0191] Using a vacuum evaporation apparatus, the pressure was reduced from atmospheric pressure to 1×10⁻⁶. -5 A magnesium vapor deposition film with a thickness of 200 angstroms is formed on one side of a biaxially oriented polyolefin film or PET film using magnesium as the vapor deposition source via vacuum vapor deposition. At this time, the pressure is measured from atmospheric pressure to 1 × 10⁻⁶. -5 In addition to the time allotted, the unevenness of the metal film surface is visually inspected, and the yield is evaluated according to the following standards. Regarding the evaluation criteria, A is evaluated as acceptable, and B is evaluated as unacceptable.
[0192] A: Decompression from atmospheric pressure to 1×10 -5 The time for application was less than 50 minutes, and no irregularities were observed on the surface of the metal film.
[0193] B: Decompression from atmospheric pressure to 1×10 -5 The time required to hold the film is greater than 50 minutes, or unevenness can be observed on the surface of the metal film.
[0194] (Polypropylene resin, etc.)
[0195] The raw materials and their properties used in the biaxially oriented polyolefin films of the Examples and Comparative Examples are shown in Tables 1 and 2 below. It should be noted that these property values are obtained by evaluating the resin granules. It should also be noted that two types of polypropylene resin granules were prepared by pre-mixing (mixing was performed by feeding them into a twin-screw extruder after dry mixing, mixing at 260°C, and then cooling).
[0196] Homopolymer polypropylene resin 1 (PP1): manufactured by Polymer Corporation
[0197] Homopolymer polypropylene resin 2 (PP2): Manufactured by Polymer Corporation
[0198] Homopolymer polypropylene resin 3 (PP3): Manufactured by Polymer Corporation
[0199] Homopolymer polypropylene resin 4 (PP4): Manufactured by Polymer Corporation
[0200] Homopolymer polypropylene resin 5 (PP5): Made by Polymer Co., Ltd. ("Polypropylene" (registered trademark) F113G)
[0201] Homopolymer polypropylene resin 6 (PP6): Manufactured by Sumitomo Chemical Co., Ltd. (Sumitomo "Nobleman" (registered trademark) FLX80E4)
[0202] Branched chain polypropylene resin 7 (PP7): Manufactured by Voliales Co., Ltd.
[0203] Polypropylene resin 8 (PP8): It is added to a twin-screw extruder at a ratio of PP1 / PP7=99.7 / 0.3, and after mixing and cooling at 260℃, granules are obtained.
[0204] Polypropylene resin 9 (PP9): PP1 / PP2 are fed into a twin-screw extruder at a ratio of 20 / 80 (by mass), and after mixing and cooling at 260°C, granules are obtained.
[0205] Polyolefin resin 1 (PO1): Propylene-1-butene copolymer manufactured by Mitsui Chemicals Co., Ltd.
[0206] 4-Methyl-1-pentene polymer 1 (PMP1): Manufactured by Mitsui Chemicals Co., Ltd.
[0207] 4-Methyl-1-pentene polymer 2 (PMP2): Manufactured by Mitsui Chemicals Co., Ltd.
[0208] 4-Methyl-1-pentene polymer 3 (PMP3): Manufactured by Mitsui Chemicals Co., Ltd.
[0209] 4-Methyl-1-pentene polymer 4 (PMP4): Manufactured by Mitsui Chemicals Co., Ltd.
[0210] 4-Methyl-1-pentene polymer 5 (PMP5)
[0211] 4-Methyl-1-pentene polymer 6 (PMP6): Manufactured by Mitsui Chemicals Co., Ltd.
[0212] 4-Methyl-1-pentene-propylene copolymer 1 (MP-P1): Manufactured by Mitsui Chemicals Co., Ltd.
[0213] 4-Methyl-1-pentene-propylene copolymer 2 (MP-P2)
[0214] (Example 1)
[0215] Polypropylene resin 8 (PP8) is supplied to a single-screw extruder for the base layer (layer A), while 4-methyl-1-pentene polymer 1 (PMP1) is supplied separately to a single-screw extruder for the surface layer (layer B). The resin mixtures for each layer are melt-extruded at 260°C. After removing impurities using a sintered filter with a 20 μm pore size, the mixture is laminated using a feed block type B / A / B composite T-die, with a thickness ratio of 1 / 48 / 1 for the surface layer (layer B) / base layer (layer A) / surface layer (layer B). The resulting melt laminate is then formed into a sheet using the T-die. The molten sheet is then discharged from the T-die into a casting drum with a surface temperature controlled at 60°C. Compressed air at 25°C is injected at an air velocity of 140 m / s using an air knife to ensure close contact between the molten sheet and the casting drum, resulting in an unstretched sheet. Next, the unstretched sheet was preheated to 156°C using ceramic rollers, and then stretched along its length at a ratio of 4.3 times between rollers at 155°C with a circumferential speed difference. It was then further relaxed by 5.2% along its length using the 155°C rollers with a circumferential speed difference to obtain a uniaxially stretched film. Next, the uniaxially stretched film was clamped at both ends in the width direction and fed into a tenter frame. After preheating at 180°C for 10 seconds, it was stretched along its width direction to 9.8 times its original length at 177°C, and then heat-fixed at 178°C while being relaxed by 13% along its width direction. After a cooling process at 100°C, it was fed onto the outside of the tenter frame, the clamps at both ends in the width direction were released, and it was wound onto a core to obtain a biaxially oriented polyolefin film with a thickness of 50 μm. The physical properties and evaluation results of the obtained biaxially oriented polyolefin film are shown in Table 3.
[0216] (Examples 2-5, Comparative Examples 1-5)
[0217] The raw material composition and film-forming conditions for each layer are shown in Table 3. Otherwise, a biaxially oriented polyolefin film was obtained in the same manner as in Example 1. It should be noted that in Example 5, PP1: 60 parts by weight, PP2: 34 parts by weight, and PMP-1: 6.0 parts by weight were mixed in granular form and fed into an extruder. In this case, the thickness was adjusted by regulating the discharge rate during extrusion and the speed of the casting drum. The physical properties and evaluation results of the obtained biaxially oriented polyolefin film are shown in Table 3. It should be noted that the thickness was adjusted by regulating the discharge rate of the extruder and the speed of the casting drum.
[0218] (Comparative Example 6)
[0219] Using PET film "Lumira" (registered trademark) S10 (manufactured by Toray Industries, Inc.) instead of biaxially oriented polyolefin film, we evaluated its heat resistance properties, yield during metal film formation, and measured its moisture content. The evaluation results are shown in Table 3.
[0220] It should be noted that, regarding the moisture content and the yield during metal film manufacturing, only Examples 1, 4, and 6 were evaluated.
[0221]
[0222] In the table, the contact angles I and Sdr of diiodomethane were measured on the surface (the side in contact with the casting drum) and the back side (the side opposite to the surface), and the measured values were recorded.
[0223] Industrial applicability
[0224] As described above, the biaxially oriented polyolefin film of the present invention can be used in various applications such as packaging film, release film, process film, hygiene products, agricultural products, construction products, and medical products. In particular, due to its excellent heat resistance, the biaxially oriented polyolefin film of the present invention can be preferably used as a release film and process film for high-temperature applications where biaxially oriented polyolefin films are generally difficult to use.
[0225] Symbol Explanation
[0226] 1: SUS board
[0227] 2: Measurement of the target membrane
[0228] 3: Thick paper
[0229] 4: Direction of pressurization
Claims
1. A biaxially oriented polyolefin film, characterized in that, The proportion S of the heat of fusion in the range of 175~190℃ obtained by differential scanning calorimetry is 10%~70% in the heat of fusion in the range of 30~190℃. There are two layers with different contents of 4-methyl-1-pentene polymer. When the layer with a relatively small content of 4-methyl-1-pentene polymer is designated as layer A and the layer with a relatively large content of 4-methyl-1-pentene polymer is designated as layer B, layer B is located on at least one film surface and layer B contains 4-methyl-1-pentene polymer as the main component.
2. The biaxially oriented polyolefin film according to claim 1, wherein the unfolded area ratio Sdr of at least one of the film surfaces is 0.2 to 10.
0.
3. The biaxially oriented polyolefin film according to claim 1 or 2, wherein at least one of the film surfaces has a static contact angle I with diiodomethane of 60 to 90°.
4. The biaxially oriented polyolefin film according to any one of claims 1 to 3, wherein when the main orientation axis direction is designated as the X direction and the main orientation orthogonal direction is designated as the Y direction, the sum of the Young's modulus in the X direction and the Young's modulus in the Y direction, E X+Y The range is 5.2~15 GPa.
5. The biaxially oriented polyolefin film according to any one of claims 1 to 4, wherein the heat of fusion H in the range of 190 to 260°C, as determined by differential scanning calorimetry, is 0.1 to 20 J / g.
6. The biaxially oriented polyolefin film according to any one of claims 1 to 5, wherein the sum of the shrinkage stress at 160°C in the X direction and the shrinkage stress at 160°C in the Y direction, as determined by thermomechanical analysis, is P. X+Y The pressure ranges from -1.0 to 3.0 MPa.
7. The biaxially oriented polyolefin film according to any one of claims 1 to 6, wherein the polyolefin resin contained therein satisfies all of the following characteristics 1 to 3: Feature 1: The melting point Tm1 with the highest peak intensity obtained in the 2nd run of differential scanning calorimetry, performed at a heating rate of 20℃ / min, is 165.0~170.0℃; Feature 2: The content of components with a molecular weight M of less than 5.0 (LogM) is 30.0-39.0% by mass. Feature 3: The proportion of components with a molecular weight M of 6.0 or higher is 3.0 to 10% by mass.
8. The biaxially oriented polyolefin film according to any one of claims 1 to 7, formed by bonding the A layer and the B layer, wherein the 4-methyl-1-pentene polymer possesses the following characteristics 4 and 5: Feature 4: The melting point Tm2 observed above 190℃ in the second run of differential scanning calorimetry performed at a heating rate of 20℃ / min is 200~250℃; Feature 5: The angular frequency ω with a loss tangent of 1 obtained by melt viscoelasticity measurement performed at 260°C. 260 The value is 1~500 rad / s.
9. A release film comprising the biaxially oriented polyolefin film according to any one of claims 1 to 8.
10. The release film according to claim 9, used in fiber-reinforced composite materials, substrates, or molds.
11. A process membrane comprising the biaxially oriented polyolefin membrane according to any one of claims 1 to 8.
12. A laminate formed by bonding a metal film to at least one surface of a biaxially oriented polyolefin film according to any one of claims 1 to 8.
13. The laminate according to claim 12, wherein the metal film comprises a metal belonging to Group 1 or Group 2 of the periodic table.
14. A laminate formed by bonding a transparent conductive film to at least one surface of a biaxially oriented polyolefin film according to any one of claims 1 to 8.
15. A laminate formed by contacting an electrolyte membrane with at least one surface of a biaxially oriented polyolefin membrane according to any one of claims 1 to 8.
16. The laminate according to claim 15, wherein the electrolyte membrane is used in a fuel cell, a semi-solid cell, or a bulk cell.
17. A current collector formed using a biaxially oriented polyolefin film according to any one of claims 1 to 8.
18. A storage battery formed using a biaxially oriented polyolefin film according to any one of claims 1 to 8.
Citation Information
Patent Citations
Biaxially oriented polypropylene film
JP2014030974A
Polypropylene multilayer stretched film
JP2015044406A
Multilayer polypropylene film
WO2018097161A1
